2022
DOI: 10.1101/2022.02.07.22270652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marker genes of incident type 1 diabetes in peripheral blood mononuclear cells of children: A machine learning strategy for large-p, small-n scenarios

Abstract: Background and objective: Type 1 diabetes (TID) is a complex, polygenic disorder, the etiology of which is not fully elucidated. Machine learning (ML) genomics could provide novel insights on disease dynamics while high-dimensionality remains a challenge. This study aimed to identify marker genes of incident T1D in peripheral blood mononuclear cells (PBMC) of children via a ML strategy attuned to high-dimensionality. Methods: Using samples from 105 children (81 with incident T1D and 24 healthy controls), we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Secondly, to compare our approach to a case:control cohort study not included in our analysis, we retrieved a list of genes shown by Mehdi and colleagues ( Mehdi et al., 2018 ) to be downregulated in T1D subjects relative to control individuals. Thirdly, to demonstrate the value of C-FLEE over other network informatic approaches, we identified a set of 1003 candidate T1D genes from a recent gene expression profiling meta-analysis ( De Silva et al., 2022 ). As an independent, objective benchmark, we compared enrichment of ET1DREs and these three gene sets against the Type 1 Diabetes Knowledge Portal list of 1000 genes that exhibit significant ( p < 5E-03) associations with the incidence of type 1 diabetes ( Table S20 , columns A&B).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, to compare our approach to a case:control cohort study not included in our analysis, we retrieved a list of genes shown by Mehdi and colleagues ( Mehdi et al., 2018 ) to be downregulated in T1D subjects relative to control individuals. Thirdly, to demonstrate the value of C-FLEE over other network informatic approaches, we identified a set of 1003 candidate T1D genes from a recent gene expression profiling meta-analysis ( De Silva et al., 2022 ). As an independent, objective benchmark, we compared enrichment of ET1DREs and these three gene sets against the Type 1 Diabetes Knowledge Portal list of 1000 genes that exhibit significant ( p < 5E-03) associations with the incidence of type 1 diabetes ( Table S20 , columns A&B).…”
Section: Resultsmentioning
confidence: 99%